Diaphragm modified material and preparation method thereof, diaphragm and sodium battery

The porous silica-loaded nickel powder material prepared by using the sol-gel method in the sodium ion battery separator has solved the problem of gas extraction of sodium ion battery, extending the battery life and improving the performance of the separator.

CN119812667AActive Publication Date: 2025-04-11JIANGSU PYLON BATTERY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510282770.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-11
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

Sodium ion batteries have serious gas extraction problems, especially under high temperature conditions, the CO and CO2 gases produced are poor reversible, resulting in a shortening of battery life.

Method used

Silica with a porous structure is prepared by sol-gel method, and nickel powder is supported in the pores of the silica to form a separator-modified material. The material is able to adsorb water and gas generated in the cell and store the carbonylated nickel liquid through reaction of nickel powder with CO.

Benefits of technology

Effectively absorb water and gas generated during charging and discharging, reduce the expansion of the sodium battery volume, extend the service life of the battery, and improve the puncture strength, corrosion resistance, safety and electric field uniformity of the diaphragm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812667A_ABST
    Figure CN119812667A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, and discloses a diaphragm modified material, a preparation method thereof, a diaphragm and a sodium battery. The preparation method comprises the steps that a first mixed solution is gradually added into a second mixed solution for full reaction, a third mixed solution is obtained, the first mixed solution is an alcoholic solution with the pH of 11-12.5, and the second mixed solution comprises monoalkyl silicate ester and nickel powder dispersed in the monoalkyl silicate ester; stirring the third mixed solution at 60-90 DEG C until a colloidal mixture is obtained; freeze-drying the colloidal mixture to remove moisture in the colloidal mixture to obtain a porous silicon dioxide composite material loaded with nickel powder; the mass ratio of the monoalkyl silicate ester to the nickel powder is (2.5-9): 1. Compared with a conventional diaphragm, the diaphragm prepared by coating the diaphragm modified material prepared by the preparation method on the surface of a base diaphragm as a modifier can improve the volume expansion of a battery and prolong the service life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a diaphragm modified material and a preparation method thereof, a diaphragm and a sodium battery. Background Art

[0002] Sodium ion batteries are batteries that use layered oxides (such as nickel iron manganese oxide and copper iron manganese oxide) materials, Prussian blue analogs (such as iron-based Prussian white, etc.), polyanions (such as sodium iron sulfate, sodium iron phosphate, etc.) as positive electrodes, and carbon materials (such as hard carbon, soft carbon) as negative electrodes. They mainly use esters and ethers as solvents. + Metal salts (such as sodium fluoride salts, sodium borate salts and perchlorates) electrolytes and various additives (such as film-forming, flame retardant and overcharge protection) form an electrolyte. Although sodium ion batteries and their negative electrode-free batteries have the advantages of good low-temperature performance, low cost, high safety and long cycle life, they still have serious gas evolution problems, among which high-temperature gas evolution is more obvious. In particular, the reversibility of gases such as CO and CO2 produced is poor, which will not only accumulate inside the battery cell, but also decompose the electrolyte components, affecting the battery life. In addition, iron-based materials such as polyanions (such as sodium ferric sulfate, sodium ferric phosphate pyrophosphate, etc.) have strong water absorption capacity, and H2O is also easy to decompose and produce gas.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The object of the present invention is to provide a diaphragm modified material and a preparation method thereof, a diaphragm and a sodium battery, aiming to improve at least one of the problems mentioned in the background technology.

[0005] The present invention is achieved in that: In a first aspect, an embodiment of the present invention provides a method for preparing a membrane modified material, comprising: gradually adding the first mixed solution to the second mixed solution for sufficient reaction to obtain a third mixed solution, wherein the first mixed solution is an alcohol solution with a pH of 11 to 12.5, and the second mixed solution includes a monoalkyl silicate and nickel powder dispersed in the monoalkyl silicate; Stirring the third mixed solution at 60-90° C. until a colloidal mixture is obtained; The colloidal mixture is freeze-dried to remove water therein, thereby obtaining a porous silica composite material loaded with nickel powder; The mass ratio of monoalkyl silicate to nickel powder is 2.5~9:1.

[0006] In an optional embodiment, the first mixed solution is prepared by: Ammonia water was added to the mixture of alcohol and water to adjust the pH to 11-12.5.

[0007] In an optional embodiment, at least one of the following features (1) and (2) is included: (1) The alcohol is at least one selected from methanol, ethanol, n-butanol and n-propanol; (2) The mass ratio of alcohol to water is 1.5~8:1.

[0008] In an optional embodiment, at least one of the following features (1) to (5) is included: (1) The monoalkyl silicate is selected from at least one of ethyl orthosilicate and methyl orthosilicate; (2) The second mixed solution also contains hydroxide dispersed therein, and the mass ratio of hydroxide to monoalkyl silicate is 9 to 19:1; (3) the hydroxide is selected from at least one of sodium hydroxide and calcium hydroxide; (4) The particle size of nickel powder is 80~120nm; (5) Stir the third mixed solution at 60-90° C. for 11-14 h to obtain a colloidal mixture.

[0009] In a second aspect, an embodiment of the present invention provides a diaphragm modified material, which is prepared by a preparation method provided by any embodiment of the present invention.

[0010] In a third aspect, an embodiment of the present invention provides a diaphragm, comprising a base film and a modified coating coated on the surface of the base film, wherein the modified coating contains the diaphragm modified material provided by an embodiment of the present invention.

[0011] In an optional embodiment, the components of the modified coating include 9 to 19 parts of the membrane modification material and 1 part of the adhesive, by weight.

[0012] In an optional embodiment, at least one of the following features (1) to (4) is included: (1) The base film is made of polyethylene, polypropylene or glass fiber; (2) The adhesive is selected from at least one of PVDF, CMC and SBR; (3) The thickness of the modified coating is 2~4μm; (4) The surface density of the modified coating is 2~4 mg / cm 2 .

[0013] In a fourth aspect, an embodiment of the present invention provides a sodium battery, comprising the diaphragm provided by any of the aforementioned embodiments.

[0014] In an optional embodiment, the sodium battery includes at least one of the following features (1) to (3): (1) Sodium batteries are sodium ion batteries or sodium metal batteries; (2) The positive electrode active material of the sodium battery is a polyanion material, a layered oxide or a Prussian blue analogue; (3) Sodium battery is a sodium ion battery, and the sodium salt in its electrolyte is sodium hexafluorophosphate.

[0015] The present invention has the following beneficial effects: The preparation method provided by the present invention is to prepare porous silica by a sol-gel method. Since nickel powder is dispersed in a solution during the preparation process, the nickel powder is loaded in the pores of silica in the obtained finished product. The porous silica prepared by the sol-gel method has strong hydrophilicity and adsorption, and can well adsorb water and gas generated in the battery, and the nickel powder can react with CO at room temperature (equation: CO + 4Ni=Ni(CO)4) to convert into carbonyl nickel liquid stored in silica. Therefore, when the diaphragm modified material prepared by the present invention is applied to the diaphragm of a sodium battery (such as a sodium ion battery or a negative electrode-free sodium metal battery), it can effectively absorb water and gas generated during charging and discharging, greatly reduce the expansion of the volume of the sodium battery, and extend the service life of the battery. In addition, the modified material mainly composed of silicon dioxide is coated on the surface of the diaphragm to improve the puncture strength, corrosion resistance, safety and electric field uniformity of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 This is the SEM of the membrane modified material prepared in Example 1. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0019] The following is a detailed description of the diaphragm modified material and its preparation method, diaphragm and sodium battery provided by the present invention.

[0020] An embodiment of the present invention provides a method for preparing a membrane modified material, comprising: gradually adding the first mixed solution to the second mixed solution for sufficient reaction to obtain a third mixed solution, wherein the first mixed solution is an alcohol solution with a pH of 11 to 12.5, and the second mixed solution includes a monoalkyl silicate and nickel powder dispersed in the monoalkyl silicate; Stirring the third mixed solution at 60-90° C. until a colloidal mixture is obtained; The colloidal mixture is freeze-dried to remove water therein, thereby obtaining a porous silica composite material loaded with nickel powder; The mass ratio of monoalkyl silicate to nickel powder is 2.5~9:1.

[0021] The preparation method provided by the present invention is to prepare silica with a porous structure by a sol-gel method. Since nickel powder is dispersed in a solution during the preparation process, the nickel powder is loaded in the pores of silica in the obtained finished product. The porous silica prepared by the sol-gel method has strong hydrophilicity and adsorption, and can well adsorb water and gas generated in the battery, and the nickel powder can react with CO at room temperature (equation: CO + 4Ni=Ni(CO)4) to convert into carbonyl nickel liquid. After the modified material is applied to the diaphragm, the gas generated during the charging and discharging process of the battery is adsorbed into its pores by silica, and the carbonyl nickel liquid generated by the reaction of CO gas entering the pores with nickel powder is stored in the pores of silica. Silica acts as both a gas collector and a storage device for carbonyl nickel, reducing the contact between gas and carbonyl nickel and the original battery system, and reducing unnecessary side reactions. Therefore, porous silica and nickel powder work together to reduce the effect of reducing gas generation. Therefore, when the diaphragm modified material prepared by the present invention is used in the diaphragm of a sodium battery (such as a sodium ion battery or a negative electrode-free sodium metal battery), it can effectively absorb water and gas generated during the charging and discharging process, greatly reduce the volume expansion of the sodium battery, and extend the service life of the battery. In addition, the modified material mainly composed of silicon dioxide is coated on the surface of the diaphragm to improve the puncture strength, corrosion resistance, safety and electric field uniformity of the diaphragm.

[0022] It should be emphasized that it has been found that only the sol-gel method can be used to load nickel powder into the pores of silica. Other methods such as ball milling can only achieve simple mixing of silica and nickel powder, and it is difficult to load nickel powder into the pores of silica.

[0023] It should be noted that the mass ratio of monoalkyl silicate to nickel powder should be within the range defined by the present invention. If the mass of nickel powder is too small, the gas absorption effect is not significant. If the mass of nickel powder is too large, the proportion of silicon dioxide is small, its gas adsorption capacity decreases, and the cost is unnecessarily increased.

[0024] The preparation method is specifically as follows: S1. Providing a first mixed solution Alcohol and water are mixed and stirred uniformly at a mass ratio of 1.5 to 8:1 (eg, 1.5:1, 3:1, 5:1 or 8:1), and then a pH adjuster is added to adjust the pH of the solution to 11 to 12.5 to obtain a first mixed solution.

[0025] Under alkaline conditions (such as adding ammonia water to adjust the pH to alkaline), the hydrolysis reaction rate is moderate and the polycondensation reaction rate is accelerated. The alkaline environment provided by ammonia water can make the silanol groups (Si-OH) produced by the hydrolysis of ethyl orthosilicate more susceptible to polycondensation reaction, forming Si-O-Si bonds, thereby promoting the transformation of sol to gel. Under appropriate alkaline conditions, the particle surface carries a negative charge, and the electrostatic repulsion between particles can prevent excessive aggregation of particles, which is conducive to the formation of smaller and uniform silica particles, thereby affecting the microscopic morphology and specific surface area of ​​the final product.

[0026] Optionally, the pH adjuster is aqueous ammonia.

[0027] Optionally, the alcohol is selected from at least one of methanol, ethanol, n-butanol and n-propanol.

[0028] S2. Providing a second mixed solution The monoalkyl silicate and high-purity nickel powder are mixed and stirred for 30 to 90 minutes (eg, 30 minutes, 60 minutes or 90 minutes) to obtain a second mixed solution.

[0029] To ensure that the modified diaphragm material has good performance, the mass ratio of monoalkyl silicate to high-purity nickel powder is 2.5~9:1 (e.g., 2.5:1, 5:1, 7:1 or 9:1).

[0030] Optionally, to ensure that the nickel powder can be fully loaded in the pores of silica, the particle size of the nickel powder is 80-120 nm.

[0031] Optionally, the monoalkyl silicate is selected from at least one of ethyl orthosilicate and methyl orthosilicate.

[0032] Optionally, hydroxide is also dispersed in the second mixed liquid, and the mass ratio of hydroxide to monoalkyl silicate is 9-19:1 (eg, 9:1, 15:1 or 19:1).

[0033] Optionally, the hydroxide is selected from at least one of sodium hydroxide and calcium hydroxide.

[0034] When hydroxide is dispersed in the second mixed liquid, the hydroxide is dispersed in the pores of the prepared porous silica. The hydroxide has strong water absorption. The CO2 gas generated during the charging and discharging process of the battery can react with the wet sodium hydroxide to generate carbonate compounds or water, which can further alleviate the volume expansion of the battery.

[0035] Optionally, in order to ensure the purity of nickel powder, before preparing the second mixed solution, the nickel powder is treated with hydrochloric acid to remove the oxide layer on the surface of the nickel powder, and then the nickel powder is washed with pure water for multiple times to remove the acid on the surface of the nickel powder.

[0036] S3, mixed reaction The first mixed solution is gradually added to the second mixed solution, and the mixture is fully reacted to obtain a third mixed solution.

[0037] Optionally, the specific method of gradually adding is to slowly add dropwise using a burette.

[0038] In this step, the ethoxy group (-OC2H5) in the ethyl orthosilicate molecule is replaced by the hydroxyl group (-OH) in the water molecule, and the silanol group (Si-OH) produced by hydrolysis is more susceptible to polycondensation reaction.

[0039] S4, make colloid The third mixed liquid is stirred at 60-90° C. (eg, 60° C., 70° C., 80° C. or 90° C.) for 11-14 h (eg, 11 h, 12 h or 14 h) to obtain a colloidal mixture.

[0040] The silanol groups (Si-OH) produced by hydrolysis in this step are more likely to undergo polycondensation. As the reaction proceeds, the viscosity of the system gradually increases, forming a sol, which further reacts to form a gel. This step needs to be carried out at 60-90°C (for example, 60°C, 70°C, 80°C or 90°C). If the temperature is too high or too low, a colloidal mixture cannot be generated.

[0041] S4. Freeze drying The colloidal mixture is placed in a freezer at -12 to -8°C (e.g., -12°C, -10°C, or -8°C) for 4 to 8 hours (e.g., 4 hours, 6 hours, or 8 hours) to lower its temperature, and then the water is sublimated in a freeze-drying device to obtain a porous silica diaphragm modified material with nickel powder and hydroxide loaded in the pores.

[0042] The diaphragm modified material provided by the embodiment of the present invention is prepared by the preparation method provided by the embodiment of the present invention.

[0043] The membrane modified material is applied in battery membranes to improve battery expansion and extend the service life of the battery.

[0044] The diaphragm provided by the embodiment of the present invention comprises a base film and a modified coating layer coated on the surface of the base film, wherein the modified coating layer contains the diaphragm modified material provided by the embodiment of the present invention.

[0045] Since the modified coating of the separator contains the modified material improved by the present invention, the separator can be applied to the battery to give the battery better electrochemical performance.

[0046] Optionally, the components of the modified coating include 9 to 19 parts of diaphragm modification materials and 1 part of adhesive, by weight.

[0047] Optionally, the base film is made of polyethylene, polypropylene or glass fiber; Optionally, the adhesive is selected from at least one of PVDF, CMC and SBR; Optionally, in order to make the separator have better performance, the thickness of the modified coating is 2-4 μm (eg, 2 μm, 3 μm or 4 μm).

[0048] Optionally, in order to make the separator have better performance, the surface density of the modified coating is 2-4 mg / cm 2 (e.g. 2 mg / cm 2 、3mg / cm 2 or 4 mg / cm 2 ). Further, the preparation method of the diaphragm is: The membrane modification material, the adhesive and pure water are uniformly mixed to prepare a slurry having a solid content of 30 to 40% (e.g., 30%, 35% or 40%); The slurry was evenly sprayed on the surface of the base film using a diaphragm spray / roll coating apparatus, and then baked in an oven at 95°C for 2 hours, and finally rolled by a roller press to obtain the diaphragm.

[0049] The sodium battery provided by the embodiment of the present invention includes the diaphragm provided by the embodiment of the present invention.

[0050] Optionally, the sodium battery is a sodium ion battery or a sodium metal battery; Optionally, the positive active material of the sodium battery is a polyanion material, a layered oxide or a Prussian blue analog; Optionally, the sodium battery is a sodium ion battery, and the sodium salt in the electrolyte is sodium hexafluorophosphate, for example: 1MNaPF6+EC / DMC / VC (or 1M NaPF6+diethylene glycol dimethyl ether).

[0051] Optionally, the negative electrode is a hard carbon material coated negative electrode or an aluminum foil current collector serves as the negative electrode.

[0052] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0053] Example 1 Ethanol and pure water are mixed in a mass ratio of 6:1 to obtain an alcohol solution, and 0.1 M ammonia water is added dropwise as a pH adjuster to the alcohol solution to adjust the pH value to 12 to obtain a first mixed solution; The second mixed solution is obtained by uniformly mixing tetraethyl orthosilicate, nickel powder with a particle size of 80 to 120 nm, and calcium hydroxide, wherein the mass ratio of tetraethyl orthosilicate to nickel powder is 8:2, and the mass ratio of tetraethyl orthosilicate to calcium hydroxide is 9:1; Add the first mixed solution dropwise to the second mixed solution and fully react to obtain a third mixed solution; The third mixed solution was stirred at 60° C. for 14 h to obtain a colloidal mixture; The colloidal mixture was placed in a freezer at -10°C for 6 hours and then freeze-dried to obtain a porous silica membrane modified material loaded with nickel powder and calcium hydroxide. The SEM image is shown in FIG. Figure 1 As shown, it can be seen from the figure that the spherical silicon dioxide particles are coated with nickel powder and hydroxide.

[0054] The prepared membrane modification material, PVDF and pure water were evenly mixed to prepare a slurry with a solid content of 30%, wherein the mass ratio of the membrane modification material to PVDF was 15:1.

[0055] The slurry was sprayed onto the surface of the polyethylene film, baked in an oven at 95°C for 2 h, and then rolled to obtain a coating with a surface density of 3 mg / cm 2 , the modified coating thickness is 3μm.

[0056] Example 2 Methanol and pure water are mixed at a mass ratio of 8:1 to obtain an alcohol solution, and 0.06M ammonia water is added dropwise as a pH adjuster to the alcohol solution to adjust the pH value to 11 to obtain a first mixed solution; The second mixed solution is obtained by uniformly mixing tetraethyl orthosilicate, nickel powder with a particle size of 80 to 120 nm, and sodium hydroxide, wherein the mass ratio of tetraethyl orthosilicate to nickel powder is 7:3, and the mass ratio of tetraethyl orthosilicate to calcium hydroxide is 9:1; Add the first mixed solution dropwise to the second mixed solution and fully react to obtain a third mixed solution; The third mixed solution was stirred at 90° C. for 10 h to obtain a colloidal mixture; The colloidal mixture was placed in a freezer at -10°C for 6 hours, and then freeze-dried to obtain a porous silica membrane modified material loaded with nickel powder and sodium hydroxide.

[0057] The prepared membrane modification material, PVDF and pure water were evenly mixed to prepare a slurry with a solid content of 25%, wherein the mass ratio of the membrane modification material to PVDF was 19:1.

[0058] The slurry was sprayed onto the surface of the polyethylene film, baked in an oven at 95°C for 2 h, and then rolled to obtain a coating with a surface density of 2 mg / cm 2, the modified coating thickness of the diaphragm is 2μm.

[0059] Example 3 n-Propanol and pure water are mixed at a mass ratio of 4:1 to obtain an alcohol solution, and 1.2M ammonia water is added dropwise as a pH adjuster to the alcohol solution to adjust the pH value to 12.5 to obtain a first mixed solution; The second mixed solution is obtained by uniformly mixing tetraethyl orthosilicate, nickel powder with a particle size of 80 to 120 nm, and sodium hydroxide, wherein the mass ratio of tetraethyl orthosilicate to nickel powder is 9:1, and the mass ratio of tetraethyl orthosilicate to calcium hydroxide is 9:1; Add the first mixed solution dropwise to the second mixed solution and fully react to obtain a third mixed solution; The third mixed solution was stirred at 75° C. for 12 h to obtain a colloidal mixture; The colloidal mixture was placed in a freezer at -10°C for 6 hours, and then freeze-dried to obtain a porous silica membrane modified material loaded with nickel powder and sodium hydroxide.

[0060] The prepared membrane modification material, PVDF and pure water were evenly mixed to prepare a slurry with a solid content of 35%, wherein the mass ratio of the membrane modification material to PVDF was 9:1.

[0061] The slurry was sprayed onto the surface of the polyethylene film, baked in an oven at 95°C for 2 h, and then rolled to obtain a coating with a surface density of 4 mg / cm 2 , the modified coating thickness is 4μm.

[0062] Example 4 This embodiment is basically the same as the embodiment 3, except that no hydroxide is added to the second mixed solution, and the obtained modified diaphragm material is a composite material in which nickel powder is loaded in the pores of porous silica.

[0063] Comparative Example 1 This comparative example provides the base film in Example 4 as a separator.

[0064] Comparative Example 2 This comparative example is basically the same as Example 4, except that: The modified diaphragm material was replaced by a mixed powder obtained by fully ball-milling nickel powder and conventional non-porous silicon dioxide powder with a particle size of 200-250 nm, wherein the ratio of nickel powder to silicon dioxide was the same as that in the modified diaphragm material prepared in Example 4.

[0065] Comparative Example 3 This comparative example is substantially the same as Example 4, except that there is no nickel powder in the second mixed solution.

[0066] Comparative Example 4 This comparative example is basically the same as Example 4, except that an equal amount of nickel powder is used to replace the modified diaphragm material to prepare the diaphragm.

[0067] Comparative Example 5 This comparative example is substantially the same as Example 4, except that the ratio of nickel powder to tetraethyl orthosilicate is 7:3.

[0068] Experimental example The diaphragms prepared in each embodiment and comparative example were made into sodium ion batteries. The preparation method of the positive electrode is: sodium ferric pyrophosphate, conductive carbon black, PVDF, and PAA are mixed evenly according to 95:2:2:1 and added to the solvent (NMP) to obtain a positive electrode slurry, and the positive electrode slurry is applied to the surface of the carbon-coated aluminum foil to obtain a positive electrode sheet. The preparation method of the negative electrode collector is: conductive carbon black, SBR, and CMC are mixed evenly according to 95:3:2 and added to the solvent (deionized water) to obtain a carbon-coated layer slurry, and the slurry is applied to the surface of the aluminum foil to obtain a negative electrode collector. The electrolyte is 1M NaPF6 + diethylene glycol dimethyl ether.

[0069] The electrochemical performance of the prepared sodium ion battery was tested and the exhaust volume was measured. The test method was the water displacement method, which was as follows: a water cylinder was placed on an electronic balance and the soft-pack battery was placed in the water, just submerged in the water. Principle: Archimedes, F 浮 =G 排 =ρ 水 V 排 , ρ 水 g=10. V 排 =1 / 10 F 浮 =The weight shown on the electronic scale (g).

[0070] Record the test results in Table 1.

[0071] Table 1 Test results of various embodiments and comparative examples

[0072] It can be seen from Table 1 that the diaphragms prepared in various embodiments of the present invention have better performance when assembled into sodium ion batteries than the diaphragm of Comparative Example 1; Comparing Comparative Example 2 with Example 4, it can be seen that the gas inhibition of Comparative Example 2 is significantly worse than that of Example 4, indicating that the effect of replacing porous silica-coated nickel powder with conventional silica-mixed nickel powder to improve the cycle performance of the diaphragm is poor; Comparing Comparative Example 3 with Example 4, it can be seen that the gas inhibition of Comparative Example 3 is significantly worse than that of Example 4, indicating that the porous silica has no nickel powder loading, and the volume expansion improvement effect of the battery is poor, and the effect of extending the battery life is poor; Comparing Comparative Example 4 with Example 4, it can be seen that the capacity retention rate and gas inhibition of Comparative Example 4 are significantly worse than those of Example 4, indicating that only nickel powder is used as a modified material to coat the surface of the diaphragm, compared with the nickel powder and porous silica working together, the capacity retention rate is worse due to the increase in self-discharge, resulting in a worse cycle life; Comparing Comparative Example 5 with Example 4, it can be seen that the capacity retention rate and gas inhibition of Comparative Example 5 are significantly worse than those of Example 4, indicating that if the amount of nickel powder used is too much, the capacity retention rate will be worse due to increased self-discharge, resulting in a worse cycle life.

[0073] In summary, the present invention prepares porous silica by a sol-gel method. Since nickel powder is dispersed in a solution during the preparation process, the nickel powder is loaded in the pores of silica in the obtained finished product. The porous silica prepared by the sol-gel method has strong hydrophilicity and adsorption, and can well adsorb water and gas generated in the battery, while nickel powder can react with CO at room temperature (equation: CO + 4Ni=Ni(CO)4) to convert into carbonyl nickel liquid stored in silica. Therefore, when the diaphragm modified material prepared by the present invention is used in the diaphragm of a sodium battery (such as a sodium ion battery or a negative electrode-free sodium metal battery), it can effectively absorb water and gas generated during charging and discharging, greatly reduce the expansion of the volume of the sodium battery, and extend the service life of the battery. In addition, the modified material mainly composed of silicon dioxide is coated on the surface of the diaphragm to improve the puncture strength, corrosion resistance, safety and electric field uniformity of the diaphragm.

[0074] In a preferred embodiment, hydroxide is added to the second mixed solution, so that the prepared porous silicon dioxide is also loaded with hydroxide, which can further improve the hygroscopicity and gas absorption of the material.

[0075] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a membrane modified material, characterized in that: include: gradually adding the first mixed solution to the second mixed solution for sufficient reaction to obtain a third mixed solution, wherein the first mixed solution is an alcohol solution with a pH of 11 to 12.5, and the second mixed solution includes a monoalkyl silicate and nickel powder dispersed in the monoalkyl silicate; Stirring the third mixed solution at 60-90° C. until a colloidal mixture is obtained; freeze-drying the colloidal mixture to remove water therein, thereby obtaining a porous silica composite material loaded with nickel powder; The mass ratio of the monoalkyl silicate to the nickel powder is 2.5-9:

1.

2. The preparation method according to claim 1, characterized in that: The preparation method of the first mixed solution is: Ammonia water was added to the mixture of alcohol and water to adjust the pH to 11-12.

5.

3. The preparation method according to claim 2, characterized in that: The invention comprises at least one of the following features (1) and (2): (1) The alcohol is at least one selected from methanol, ethanol, n-butanol and n-propanol; (2) The mass ratio of the alcohol to water is 1.5 to 8:

1.

4. The preparation method according to claim 1, characterized in that: The invention comprises at least one of the following features (1) to (5): (1) The monoalkyl silicate is selected from at least one of ethyl orthosilicate and methyl orthosilicate; (2) A hydroxide is also dispersed in the second mixed liquid, and the mass ratio of the hydroxide to the monoalkyl silicate is 9 to 19:1; (3) The hydroxide is selected from at least one of sodium hydroxide and calcium hydroxide; (4) The particle size of the nickel powder is 80-120 nm; (5) Stirring the third mixed solution at 60-90° C. for 11-14 hours to obtain the colloidal mixture.

5. A membrane modified material, characterized in that: The method is as described in any one of claims 1 to 4.

6. A diaphragm, characterized in that: It comprises a base film and a modified coating layer coated on the surface of the base film, wherein the modified coating layer contains the diaphragm modified material as claimed in claim 5.

7. The diaphragm according to claim 6, characterized in that The components of the modified coating include 9 to 19 parts of the diaphragm modification material and 1 part of the adhesive, in terms of weight.

8. The diaphragm according to claim 7, characterized in that Includes at least one of the following features (1) to (4): (1) The base film is made of polyethylene, polypropylene or glass fiber; (2) The adhesive is selected from at least one of PVDF, CMC and SBR; (3) The thickness of the modified coating is 2-4 μm; (4) The surface density of the modified coating is 2-4 mg / cm 2 .

9. A sodium battery, characterized in that: The invention comprises the diaphragm according to any one of claims 6 to 8.

10. The sodium battery according to claim 9, characterized in that: Includes at least one of the following features (1) to (3): (1) The sodium battery is a sodium ion battery or a sodium metal battery; (2) The positive electrode active material of the sodium battery is a polyanion material, a layered oxide or a Prussian blue analogue; (3) The sodium battery is a sodium ion battery, and the sodium salt in its electrolyte is sodium hexafluorophosphate.

Citation Information

Patent Citations

  • Preparation method of in-situ growth nanoparticle modified polymer diaphragm

    CN110690387A

  • Novel diaphragm coating material, preparation method thereof and lithium ion battery

    CN117650339A

  • Diaphragm, preparation method thereof and sodium ion battery

    CN118399018A

  • Method for manufacturing positive electrode complex material for lithium secondary battery, and method for manufacturing electrode using same, and method for charging and discharging same electrode

    KR1020140101915A

  • Water-based composition used for modifying diaphragm for lithium ion batteries and modified diaphragm and batteries

    US20170162848A1